Borderwaters : Amid the Archipelagic States of America - Roberts, Brian Russell (Book collections on Project MUSE., 2021)
"Brian Russell Roberts dispels continental-centric US national mythologies to advance an alternative image of the United States as an archipelagic nation to better reflect its claims to archipelagoes in the Pacific and Caribbean."--